Pengaruh Leader Member Exchange Terhadap Work Role Performance dan Innovative Work Behaviour dengan Employee Engagement Sebagai Variabel Mediasi pada Lembaga Pendidikan Nonformal Internasional Mental Aritmatika Yogyakarta - Arif Fajar Sugiarto; Prayekti Prayekti; Nala Tri Kusuma (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
This study aims to determine the effect of leader member exchange on work role performance and innovative work behavior with employee engagement as a mediating variable at the IMA Yogyakarta Nonformal Education Institute. The population in this study were employees who worked at the IMA Yogyakarta Nonformal Education Institute, totaling 60 employees using the saturated sampling technique. The data collection method uses questionnaire distribution. The results showed that leader member exchange has a positive and significant effect on employee engagement. Leader member exchange has a positive and significant effect on work role performance. Leader member exchange has a positive and significant effect on innovative work behavior. Employee engagement is not able to mediate the effect of leader member exchange on work role performance. Employee engagement is not able to mediate the effect of leader member exchange on innovative work behavior. The implications of this research hopefully can be used as a reference for non-formal educational institutions IMA Yogyakarta in improving the relationship between superiors and other employees so that the relationship between the two can improve to be better than before and can be a source of information and reference for future researchers.